AB1430-HPR Effectiveness of functional rigid taping on pain, function and kinesiophobia in patients with low back pain. (12th June 2018) - Kavak, F.M; Kavak, B.; Tonga, E.
Abstract : Background: A small number of studies in the literature suggest that rigid bands applied with different techniques in different regions are effective treatment techniques. On the other hand, there is no study of how rigid bands are effective in the treatment of acute and subacute lumbar pain. Objectives: Purpose of this study is to determine the efficiency of functional tape application to patients with acute or subacute low back pain. Methods: 40 patients with acute-subacute low back pain were divided into two groups: control and experimental group. To control group, McKenzie exercises, Transcutaneous Electrical Nerve Stimulation (TENS), Hot Pack (HP) and pulsed ultrasound treatments were applied. To experimental group, functional taping were applied in addition of these treatments. Range of Motion (ROM), Visual Analogue Scale (VAS), Tampa Scale of Kinesiophobia (TSK) and The Oswestry Disability Index (ODI) were evaluated pre- and post-treatment and datas were analysed with statistical methods. In analysis; p value was accepted p<0, 05 for t test and Mann Whitney U test process. Results: In the measurements that compared the improvement of both groups, based on pre- and post-treatment evaluations; improvement in the experimental group was significantly higher in all of these parameters of ROM, VAS, TSK and ODI than in the control group (p<0, 05). Conclusions: The use of functional rigid taping in patients with acute and subacute low back pain provided a statistically significant improvement in all measured values of patients and provide better results than the control group. However, there is a need for comparative new studies in order to measure the effectiveness of rigid taping in a more accurate way. References: [1] Faqih A, et al. Effect of rigid taping on pain angait parameters in knee osteoarthritis", International Journal of Cur Research Review, 2015, 7(1), January; 24–27. [2] Polakowski EG. Systematıc review of musculoskeletal taping methods . University Of Pittsburgh, School of Health and Rehabilitation Sciences Bachelors of Philosophy; 2015 Acknowledgements: We want to thanks to Dr Murat Dalkılıç for his support. Disclosure of Interest: None declared